The Secularization of the Estates of the Eastern Monasteries and Churches in Wallachia and Moldavia in the Early 1860-s and Russia - Gerd Lora (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is the fi rst attempt to trace in details, basing on inedited archive materials from Russian and Rumanian archives, the history of the secularization of the so called “inclined” monastic properties in the united principalities of Moldavia and Wallachia during the reign of Alexander Kuza. Attempts (though without any suffi cient result) to reduce the rights of the foreign owners of the estates (1/4 of the territory of the country) were undertaken already in the fi rst half of the 19th century. After the Crimean war with weakening of Russian infl uence and strengthening of French one such an action could count on better results. According to Protocol 13 of the Paris Conference of 1858 the Principalities should have solved their problem with the Greek owners of the properties. In case of misunderstanding an international commission consisting of commissioners from the powers had to take place. Such a commission started its work in Constantinople in 1862, and as it’s well preserved documentation shows, did not bring any positive result. Russia was the only to support the rights of the Greek owners, while the position of Britain and Austria was wavering, and France was in open opposition to any actions against the secularization. The inconsistent behavior of the Greek Patriarchs and the attempts of Patriarch Joachim II to turn the aff air in his own benefi t only was in the way of solution of the question. Another idea, of a monetary compensation for the estates was not carried through either, though the Greek bankers of Constantinople seemed ready to support it. Meanwhile Kuza, basing on the support of Napoleon III, carried through the fi nal confi scation of the lands. This act became one of the most suffi cient in his policy for unifi cation of Rumania and creating an independent national state.